How Role Conflict and Leadership Style can Affect Job Satsfaction among Community Health Service Workers in Indonesia - Rina Anindita; Tofan Tofan (Journal of Educational, Health and Community Psychology, 2020)
Employees who work in the health services are no exception; public health centers tend to experience high role conflict. Several of the previous studies and articles have raised the issue of role conflict and transformational leadership. The organization must set a strategy so then role conflict and leadership style do not become a problem that can, in time, become an obstacle in the organization. The purpose of this study is to determine if role conflict and transformational leadership style tied into job satisfaction is mediated by work stress. The study was conducted through the survey method using a questionnaire distributed in August - September 2019. The respondents in this study totaled 185 health service employees who worked in the health centers in Jakarta, Indonesia. The data was analyzed using the Structural Equation Model (SEM). The results showed that there was a relationship between role conflict and job stress, that there was a relationship between job stress and job satisfaction, that there was a relationship between transformational leadership style and job satisfaction but that there was no relationship between role conflict and job satisfaction or between transformational leadership style and work stress in the health service employees.